Odpowiedź :
a=3²×10⁵
b=10³ˣ30²
Korzystamy ze wzorów działań na potęgach
[tex](a*b)^c=a^c*b^c[/tex]
oraz
[tex]a^c*a^d=a^{c+d}[/tex]
[tex]b=10^3*30^2=10^3*(3*10)^2=10^3*3^2*10^2=3^2*(10^3*10^2)=3^2*10^{3+2}=3^2*10^5=a[/tex]
Odpowiedź:
Mamy wzory:
[tex](a*b)^{n} =a^{n} * b^{n} \\a^{n} *a^{m}=a^{n+m} \\[/tex]
czyli:
[tex]a=3^{2} *10^5[/tex]
a
[tex]b=10^3 *30^2 \\[/tex]
po przekształceniu:
[tex]b=10^3 *30^2= 10^3 * (3*10)^2=10^3*3^2*10^2=10^5*3^2\\[/tex]
czyli:
a=b
Co mieliśmy wykazać
Szczegółowe wyjaśnienie: